A novel strategy against hepatitis B virus: Glycyrrhetnic acid conjugated multi-component synergistic nano-drug delivery system for targeted therapy. (March 2023) - Guan, QingXia; Zhou, XiaoYing; Yang, FangFang; Zhang, Xue; Wang, YanHong; Li, WeiNan; Li, XiuYan
It is well known that Glycyrrhetnic acid (GA) has significant liver-targeting and anti-inflammatory effects. Syringopicroside (SYR) and Hydroxytyrosol (HT), the active components of the Chinese herb Syringa oblata Lindl, have earned great reputation for their potential in preventing or treating viral hepatitis type B. Therefore, we loaded SYR and HT into GA-conjugated PEG-PLGA, so that they could target the liver in additional to exerting their own pharmacological effects in a synergistic. However, the in vivo targeting and the low bioavailability of SYR and HT pose a huge challenge. Therefore, we synthesized GA-conjugated multi-component nano-drug delivery system (SH-GPP). SH-GPP had a regular spherical shape with a uniform size distribution of 110.5 ± 3.18 nm. We further evaluated the effects of SH-GPP in vitro and in vivo . In the in vivo experiment, we evaluated the following parameters: the serum ALT and AST values; liver tissue homogenate MDA and SOD; HE staining of the pathological liver sections; and the liver coefficient. In the in vitro studies, the following parameters were evaluated: cellular uptake of SH-GPP; wound healing/scratch assay; cellular apoptosis; cell cycle; HBsAg; and HBeAg content. SH-GPP had better anti-hepatitis B effect than Syringopicroside and hydroxytyrosol (SH) and NPP alone. The targeting ability of GA enabled HT and SYR in GPP to reach the liver accurately, and played a synergistic role to maximize their therapeutic effects. This study provides a novel strategy against hepatitis B virus, and also provides a feasible scheme for improving the low bioavailability of the active components of traditional Chinese medicine.